2017
DOI: 10.1002/cssc.201601878
|View full text |Cite
|
Sign up to set email alerts
|

A Simple Zinc Catalyst for Carbamate Synthesis Directly from CO2

Abstract: Several zinc salts were employed as catalysts for the synthesis of carbamates directly from aromatic amines, CO , and silicate esters. Zn(OAc) offered the best performance among the salts tested. The addition of an N-donor ligand such as 1,10-phenanthroline increased the yield. The best catalytic performance of Zn(OAc) can be explained by carboxylate-assisted proton activation. The interaction between the substrate and the catalyst can be observed by chemical shifts in H and N NMR spectra. Isocyanate was a key… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(37 citation statements)
references
References 112 publications
0
36
0
Order By: Relevance
“…In particular, the reactivity of anilines is generally low, which is due to the low nucleophilicity and basicity. [33] Scheme 5 shows the results of the synthesis of cyclic ureas from CO 2 + diamines. [34] Various diamines reacted with CO 2 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 to give the corresponding five-membered ring amines in high yield, which can be higher than that of non-cyclic ureas from CO 2 + amines (Scheme 4), which can be explained by the stability of the five-membered ring ureas.…”
mentioning
confidence: 99%
“…In particular, the reactivity of anilines is generally low, which is due to the low nucleophilicity and basicity. [33] Scheme 5 shows the results of the synthesis of cyclic ureas from CO 2 + diamines. [34] Various diamines reacted with CO 2 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 to give the corresponding five-membered ring amines in high yield, which can be higher than that of non-cyclic ureas from CO 2 + amines (Scheme 4), which can be explained by the stability of the five-membered ring ureas.…”
mentioning
confidence: 99%
“…Gratifyingly, the corresponding methyl N -phenylcarbamate was formed in a yield of 80% along with N′ -diphenylurea as by-product. Recently, they found that silicate ester (i.e., Si(OR) 4 ) could be incorporated with aliphatic or aromatic amines and CO 2 to synthesize N -arylcarbamate (Scheme 19b) [107]. Notably, the corresponding carbamates of aromatic amines could be obtained in a yield of up to 96%.…”
Section: Chemical Fixation Of Co2 Through C-n Bond Formationmentioning
confidence: 99%
“…Very recently Zhang et al . reported the synthesis of a wide range of ethers using aromatic/aliphatic amines and CO 2 under pressure in the presence of Lewis acidic Zn II salts as catalyst in the presence of silicon alkoxide as an alkoxide‐donating agent to the carbamate intermediate.…”
Section: Co2 Fixation Reactionsmentioning
confidence: 99%
“…[64] 2.7. Synthesis of esters, carbamates, ureas, and lactones Very recently Zhang et al [65] reported the synthesis of aw ide range of ethers using aromatic/aliphatic amines and CO 2 under pressure in the presence of Lewis acidic Zn II salts as catalyst in the presence of silicon alkoxide as an alkoxide-donating agent to the carbamate intermediate. The isolated yield of various carbamatee sters could reach 80-96 %u nder the reaction conditions used with several Zn catalysts.…”
Section: Synthesis Of Hydrocarboxylated Alkenesmentioning
confidence: 99%